The Pasture Network for Eastern and Southern Africa (PANESA): Its regional collaborative research programme - Dzowela, B.H. (1990)
The Pastures Network for Eastern and Southern Africa (PANESA) deals with forage and other feed resource development in sub-Saharan Africa. Emphasis is placed on forage germplasm evaluation and seeking entry-points of forage resources into mixed crop-livestock smallholder farmer production systems. Operational focus is on the arid/semi-arid, humid/sub-humid and highlands zones of eastern and southern Africa. The net-works mandate seek to improve the research capabilities of national institutions so as to alleviate dry season feed resources shortages. The rationale for the network's formation, country membership, mode of operation and coverage of its collaborative research programme are discussed.